Anticonvulsant, Anticholinesterase and Cytoprotective Effects of the Aqueous Extract of Lippia sidoides Cham - Cicera Janaine Camilo; Débora Odília Duarte Leite; Natália Kelly Gomes de Carvalho; José Walber Gonçalves Castro; Jane Eire Silva Alencar de Menezes; Helcio Silva dos Santos; Joanda Paolla Raimundo Silva; Daniela Ribeiro Alves; Selene Maia de Morais; Fabíola Fernandes Galvão Rodrigues; José Galberto Martins da Costa (Plants)
(1) Background: Lippia sidoides Cham is a Brazilian aromatic plant rich in phenolic compounds. In traditional medicine, its leaves are used to treat diseases of the Central Nervous System such as stress and anxiety. This study evaluates the capacity of the aqueous extract of L. sidoides as an anticonvulsant, anticholinesterase and antihemolytic agent. (2) Methods: The extract was obtained from the leaves using water as a solvent, then dried in a spray dryer. The anticonvulsant effect was evaluated in zebrafish models using the pentylenetetrazol (PTZ) method. The anticholinesterase effect was determined using the acetylcholinesterase enzyme and physostigmine as a positive control. The antihemolytic action was evaluated by exposing erythrocytes to different concentrations of NaCl in the presence and absence of the extract. (3) Results: The anticonvulsant effect was observed at a concentration of 400 mg/kg, delaying convulsive crises. In the anticholinesterase assay, a dose-dependent action and variation in the effect over time were observed, demonstrating a reversible effect of the extract. For the osmotic fragility test, the extract showed satisfactory results, providing cellular protection across all variations of NaCl concentration. (4) Conclusions: These results demonstrate the promising potential of L. sidoides extract for the development of drugs that act in the treatment of diseases that affect the Central Nervous System.